(untitled) (Comprehensive Journal of Science, 2026)
This review article provides a concise overview of the utilization of reactive core-shell nanoparticles in polymer materials. The unique core-shell structure of these nanoparticles offers improved compatibility, dispersion, and controlled release within the polymer matrix. The incorporation of reactive core-shell nanoparticles has demonstrated significant enhancements in the mechanical properties of polymers, such as increased strength and toughness. Moreover, the ability to tailor the surface functionality enables precise control over thermal stability, flame retardancy, electrical conductivity, and optical properties. The review also highlights the importance of optimizing interfacial interactions and discusses potential applications in emerging fields. Overall, this review emphasizes the significant contributions of reactive core-shell nanoparticles in advancing the properties and performance of polymer materials.